Review of Pharmacological Activity of Ephedra Gerardiana - Halima Nazar; Azalfa Amar; Mohmmad Younus; Ghazala Shaheen; Hafiz Muhammad Asif; Farah Zafar; Sultan Ayaz (Scientific Inquiry and Review, 2023)
Ephedra gerardiana (E. gerardiana,), commonly known as "Ma-huang," is a medicinal plant native to the Himalayan region. Historically, it has a long traditional use in various indigenous systems for medicinal purpose. The current review aims to summarize the present knowledge on the botanical description, phytochemistry, traditional uses, and pharmacological properties of E. gerardiana. This study was thoroughly based on previous literature and was conducted by using electronic databases such as PubMed, Scopus, and Google Scholar. Relevant studies and recently published articles up till 2020 were included in this review. E. gerardiana is a small shrub-like plant characterized by jointed stems, scale-like leaves, and cylindrical cones. It belongs to the family Ephedraceae and is commonly found in arid and semi-arid regions. Phytochemical analysis has revealed the presence of various bioactive compounds in Ephedra gerardiana, including ephedrine, pseudoephedrine, norephedrine, and methyl ephedrine. These alkaloids are primarily responsible for their pharmacological activities. In traditional medicine, Ephedra gerardiana has been used for its bronchodilatory, diaphoretic, diuretic, and thermogenic properties. Additionally, it has been employed for the treatment of respiratory disorders, namely, asthma and nasal congestion, as a stimulant. Its bioactive alkaloids, particularly ephedrine, have been extensively studied for their potential therapeutic applications. However, caution should be exercised due to the potential side effects associated with ephedrine-containing products. Further research can explore its mechanisms of action, optimize dosage regimens, and investigate potential drug interactions to ensure its safe and effective use in clinical settings.